Structural analysis for the joint of the ITER ELM coil - Zhang, Shanwen; Song, Yuntao; Wang, Zhongwei; Ji, Xiang; Zhang, Jianfeng (Fusion engineering and design, 2017)
•The FE sub-model method is feasible and rapid for the joint design.•The components meet the static and fatigue criteria.•Nuclear heat is the key factor for the joint design. The joint is an important component of the Edge Localized Modes (ELM) coils in fusion reactor, which is used to connect the ELM coils. Like the ELM coils, the joints work in an environment with high radiation levels, high temperature and high magnetic field. These joints are mainly subject to nuclear heat from the plasma and cyclic electromagnetic (EM) loads induced by the interaction of ELM coil current with magnetic fields. Take the joint of ITER ELM coil for example. In order to assure the structural integrity of joints under these loads, it is necessary to estimate the strength and fatigue of the joints. As a local model, the joint without ELM coil is investigated by the sub-model method. Results show that the finite element sub-model method is feasible and rapid for the joint design. The maximum magnetic flux intensity occurs in the axial direction for the joint local reference, which parallels with the current and corresponds to the toroidal direction of the ITER. The two areas at the top of the Inconel sleeve appear high temperature. For the joint, the conductor, jacket and sleeve can meet the static and fatigue criteria and the joint design is valid and feasible. The thermal load from the nuclear heat is the key factor for the joint design.